Diabetes impairs arterio-venous specification in engineered vascular tissues in a perivascular cell recruitment-dependent manner. (March 2017) - Altalhi, Wafa; Sun, Xuetao; Sivak, Jeremy M.; Husain, Mansoor; Nunes, Sara S.
Abstract: Cell-based tissue engineering is a potential treatment alternative for organ replacement. However, the lack of a robust vasculature, especially in the context of diseases such as diabetes, is a major hindrance to its success. Despite extensive research on the effects of diabetes in angiogenic sprouting, its effects on vessel arterio-venous (AV) specification have not been addressed. Using an engineered tissue that yields functional vessels with characteristic AV identities, we demonstrate that type 1 diabetes negatively affects vessel AV specification and perivascular cell (PVC) coverage. Blockage of PVC recruitment in normoglycemia does not affect blood flow parameters, but recapitulates the vascular immaturity found in diabetes, suggesting a role for PVCs in AV specification. The downregulation of Jagged1 and Notch3, key modulators of endothelial-perivascular interaction, observed in diabetes support this assertion. Co-culture assays indicate that PVCs induce arterial identity specification by inducing EphrinB2 and downregulating EphB4. This is antagonized by high glucose or blockage of endothelial Jagged1. Engineered tissues composed of microvessels from diabetic mice display normal PVC coverage and Jagged1/Notch3 gene expression when implanted into non-diabetic hosts. These indicate a lack of legacy effect and support the use of a more aggressive treatment of diabetes in patients undergoing revascularization therapies.